The influence of sport on the development of postural disorders in athletes - Stosic, D.; Milenkovic, S.; Zivkovic, D. (Facta Universitatis: Series Physical Education and Sport, 2011)
The high incidence of postural disorders in certain branches of sport, especially among adolescents has questioned the influence of sports activities on the postural status of athletes. Although there is still no definite opinion about the connection between sports and postural disorders, researchers have established the existence of certain factors such as amenorrhea, weakness of the joints, highly repetitive activity of sports, muscle imbalance and others that could affect the occurrence or development of some postural disorders. These factors, along with the influence of the heritage of athletes, justify the thesis of certain authors, that scoliosis, kyphosis and lordosis are multifactorial disorders.